Cholangiocarcinoma: new perspectives for new horizons. (2nd December 2021) - Rimini, Margherita; Puzzoni, Marco; Pedica, Federica; Silvestris, Nicola; Fornaro, Lorenzo; Aprile, Giuseppe; Loi, Eleonora; Brunetti, Oronzo; Vivaldi, Caterina; Simionato, Francesca; Zavattari, Patrizia; Scartozzi, Mario; et al.
ABSTRACT: Introduction: Biliary tract cancer represents a heterogeneous group of malignancies characterized by dismal prognosis and scarce therapeutic options. Area covered: In the last years, a growing interest in BTC pathology has emerged, thus highlighting a significant heterogeneity of the pathways underlying the carcinogenesis process, from both a molecular and genomic point of view. A better understanding of these differences is mandatory to deepen the behavior of this complex disease, as well as to identify new targetable target mutations, with the aim to improve the survival outcomes. The authors decided to provide a comprehensive overview of the recent highlights on BTCs, with a special focus on the genetic, epigenetic and molecular alterations, which may have an interesting clinical application in the next future. Expert opinion: In the last years, the efforts resulted from international collaborations have led to the identification of new promising targets for precision medicine approaches in the BTC setting. Further investigations and prospective trials are needed, but the hope is that these new knowledge in cooperation with the new technologies and procedures, including bio-molecular and genomic analysis as well radiomic studies, will enrich the therapeutic armamentarium thus improving the survival outcomes in a such lethal and complex disease.